Evaluation of Dynamic Properties of Fiber Reinforced Sandy Soil at High Cyclic Strains - Pankaj Kundu; Gowtham Padmanabhan; Neha Gupta (Journal of Rehabilitation in Civil Engineering)
In the recent development of synthetic and natural fiber in the industry of cement materials, polypropylene fiber become cheap and globally available. Due to its high mixability with soil and high tensile strength, it has been used for strengthening the soil. In the current investigation, cyclic triaxial experiments were performed to examine the dynamic response of fiber reinforcement in a poorly graded sand subjected to cyclic loading. Fiber reinforced sand (FR) mixtures are prepared by short polypropylene fiber of 6 mm length with different percentages of fibers (0.25%, 0.5%, and 1.0%) and compared with unreinforced sand (UR) All the samples were tested at confining pressure of 50 kPa. All samples were tested at three different axial strains 0.075%, 0.5%, and 1.125%, respectively under no drainage condition. Maximum shear modulus is found at 18.16 MPa for sand with 0.5% fiber and the damping ratio found decreased with increasing fiber content and reduced to 15% for sand with 1.0% fiber content. Also, the effect of shear strain and repetitive loading cycle on damping and shear modulus behavior is presented in this study.